Diagnostic tests for Cushing's syndrome differ from published guidelines: data from ERCUSYN. Issue 5 (May 2017) - Valassi, Elena; Franz, Holger; Brue, Thierry; Feelders, Richard A; Netea-Maier, Romana; Tsagarakis, Stylianos; Webb, Susan M; Yaneva, Maria; Reincke, Martin; Droste, Michael; Komerdus, Irina; Maiter, Dominique; et al.
Abstract : Objective: To evaluate which tests are performed to diagnose hypercortisolism in patients included in the European Registry on Cushing's syndrome (ERCUSYN), and to examine if their use differs from the current guidelines. Patients and methods: We analyzed data on the diagnostic tests performed in 1341 patients with Cushing's syndrome (CS) who have been entered into the ERCUSYN database between January 1, 2000 and January 31, 2016 from 57 centers in 26 European countries. Sixty-seven percent had pituitary-dependent CS (PIT-CS), 24% had adrenal-dependent CS (ADR-CS), 6% had CS from an ectopic source (ECT-CS) and 3% were classified as having CS from other causes (OTH-CS). Results: Of the first-line tests, urinary free cortisol (UFC) test was performed in 78% of patients, overnight 1 mg dexamethasone suppression test (DST) in 60% and late-night salivary cortisol (LSaC) in 25%. Use of LSaC increased in the last five years as compared with previous years ( P  < 0.01). Use of HDDST was slightly more frequent in the last 5 years as compared with previous years ( P  < 0.05). Of the additional tests, late-night serum cortisol (LSeC) was measured in 62% and 48-h 2 mg/day low-dose dexamethasone suppression test (LDDST) in 33% of cases. ACTH was performed in 78% of patients. LSeC and overnight 1 mg DST supported the diagnosis of both PIT-CS and ADR-CS more frequently than UFC ( P  < 0.05). Conclusions: Use of diagnostic tests for CS varies across Europe and partly differs from the currently available guidelines. It would seem pertinent that a European consensus be established to determine the best diagnostic approach to CS, taking into account specific inter-country differences with regard to the availability of diagnostic tools.